The Comparative study on Compressive strength of Self-compacting Concrete Blended with metakaolin and microsilica - Ebenezer Ngekpe, Barisua; Iboroma Z. S. Akobo; Kenneth Ucheoma Onwuama; Ubojiekere Enyindah Obunwo (IJRDO - Journal of Mechanical And Civil Engineering, 2020)
This research work examines the performance of metakaolin and microsilica as partial replacement of cement in the production of self-compacting concrete. The mix design was carried out using absolute volume method (A.V.M). Metakaolin and microsilica was used to replace cement at 0%, 5%, 10% and 15% at various water/ cementitious ratios of 0.25, 0.30, 0.35 and 0.40, while superplasticizer dosage was kept constant for all mixtures The results indicated that the mix design adopted was appropriate for the production of self-compacting concrete for both metakaolin and microsilica compressive strength 83.3mpa and 79.7mpa respectively. Metakaolin and microsilica enhanced significantly to the development of strengths. Comparatively, the increase in compressive strength of concrete mixes containing metakaolin were slightly greater than those containing microsilica at equal percentage of replacement of cement.